The prevention of the occurence of ultraviolet B (UVB) induced hypoxanthine guanidine phosphoribosyl transferase (HGPRT) mutant cells by several commercial sunscreens An in vitro study - Noor Ikhtiyati, Noor Ikhtiyati (Universitas Gadjah Mada, 1998)
This study was aimed at comparing the effect of three different SPF (Sun Protecting Factors) of sunscreens in the prevention of UVB (Ultraviolet B) Induced mutant fibroblast cells. The study was done using a simple experimental study design. Three commercially sunscreens were coated on the plate cover surface of fibroblast culture wells. Fibroblasts were isolated from ten young boy foreskins and subcultured in 3 to 5 passages. Mutagenic transformation was done by Irradiation with 6.5 J/m2 Coerman Solarium CTL 3111 as a source of UVB. In addition there were two groups which were unprotected for control group and untreated with UVB for counting cumulative population doubling ratio (cpd). Three days after UVB irradiation, the culture, except for an unirradiated group, were incubated in HGPRT (hypoxanthine guanidine phosphoribosyl transferase) enriched medium, and fibroblast which survived in those medium considered as mutant cells. Cpd was calculated based on cell multiplication of the untreated group. The ratio of mutant cell population (mcp) is quantified by dividing the number of mutant cells with cpd. The difference of mean mcp between three subgroup of sunscreens and unprotected group was analyzed with Students t test, and the difference of mean mcp among three subgroup of sunscreens was analyzed with ANOVA. The result showed that the mean mcp of sunscreen covered cultures were lower compared to the uncovered cultures and the higher SPF had lower mean of mcp significantly (P). Therefore sunscreen was proven to protect the induction of HGPRT mutant fibroblast although the protection was not totally, and the higher SPF sunscreen showed higher protection.Key words : sunscreens - SPF - UVB - HGPRT gene mutation - fibroblast culture.